Exploring the risk factors for ischemic cerebrovascular disease in systemic lupus erythematosus: A single-center case-control study - Su, Li; Qi, Zhigang; Guan, Shaochen; Wei, Lian; Zhao, Yi (Frontiers in Immunology, 2022)
Objectives: Ischemic cerebrovascular disease (ICVD) is one of the most common and severe complications in systemic lupus erythematosus (SLE). We aim to explore the risk factors for ICVD in SLE and to access the associated clinical characteristics. Methods: 44 lupus patients with ICVD (ICVD-SLE) and 80 age and sex matched lupus patients without ICVD (non-ICVD-SLE) hospitalized in our center between years 2014-2021 were enrolled. A comprehensive set of clinical and socio-demographic data were recorded. In the ICVD-SLE group, the modified Rankin score (mRS) at 90 days after the occurrence of ICVD, the brain MRI imaging and arterial ultrasonography findings were collected. Group comparisons were made with continuous variables using independent t-test or Mann-Whitney test, and categorical variables using chi-square test or Fisher exact test. Multivariate logistic regression analysis was performed to identify the risk factors for ICVD in SLE. According to the gradations of intracranial arterial stenosis (ICAS), patients with ICVD-SLE were divided into three subgroups. Subgroup comparisons were performed by one-way ANOVA test or Kruskall-Walli’s test. Results: Of the 44 patients with ICVD, 45% had large vessel ischemic stroke, 50% had symptomatic lacunar stroke, and 9% had transient ischemic attack. Multivariate logistic regression analysis showed cutaneous vasculitis (OR=7.36, 95%CI=2.11-25.65), anticardiolipin antibody (aCL) (OR=4.38, 95%CI=1.435-13.350), and lupus anticoagulant (LA) (OR=7.543,95%CI=1.789-31.808) were the risk factors, and HCQ therapy (OR=0.198, 95%CI=0.078-0.502) was the protective factor, after controlling for confounders. In subgroup analysis, no significant difference between patients of no ICAS group and severe ICAS group was observed except for diagnostic delay, while patients of moderate ICAS group were older when SLE occurred (p<0.01) with longer diagnostic delay (p<0.01), lower percentage of hypocomplementemia (p=0.05) and steroids and HCQ therapy (p=0.01, p=0.05, respectively), a trend toward lower mRS score, but higher incidence of carotid atherosclerotic plaque (p<0.01). Conclusion: Cutaneous vasculitis and antiphospholipid antibodies (aPLs) are associated with increased risk, while HCQ therapy may have protection against ICVD in SLE. Younger lupus patients with ICVD were associated with complement-mediated inflammation, and poorer outcome, requiring immunosuppressive therapy, whereas elderly ones were characterized by moderate ICAS and carotid atherosclerotic plaques.